Synthesis, preclinical assessment, and first-in-human study of [18F]d4-FET for brain tumor imaging. - Hou, Lu; Chen, Zhiyong; Chen, Fanfan; Sheng, Lianghe; Ye, Weijian; Dai, Yingchu; Guo, Xiaoyu; Dong, Chenchen; Li, Guocong; Liao, Kai; Li, Yinlong; Ma, Jie; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: Tumor-to-background ratio (TBR) is a critical metric in oncologic PET imaging. This study aims to enhance the TBR of [18F]FET in brain tumor imaging by substituting deuterium ("D") for hydrogen ("H"), thereby improving the diagnostic sensitivity and accuracy. Methods: [18F]d4-FET was synthesised by two automated radiochemistry modules. Biodistribution studies and imaging efficacy were evaluated in vivo and ex vivo in rodent models, while metabolic stability and radiation dosimetry were assessed in non-human primates. Additionally, preliminary imaging evaluations were carried out in five brain tumor patients: three glioma patients underwent imaging with both [18F]d4-FET and [18F]FET, and two patients with brain metastases were imaged using [18F]d4-FET and [18F]FDG. Results: [18F]d4-FET demonstrated high radiochemical purity and yield. PET/MRI in rodent models demonstrated superior TBR for [18F]d4-FET compared to [18F]FET, and autoradiography showed tumor margins that correlated well with pathological extents. Studies in cynomolgus monkeys indicated comparable in vivo stability and effective dose with [18F]FET. In glioma patients, [18F]d4-FET showed enhanced TBR, while in patients with brain metastases, [18F]d4-FET displayed superior lesion delineation compared to [18F]FDG, especially in smaller metastatic sites. Conclusion: We successfully synthesized the novel PET radiotracer [18F]d4-FET, which retains the advantageous properties of [18F]FET while potentially enhancing TBR for glioma imaging. Preliminary studies indicate excellent stability, efficacy, and sensitivity of [18F]d4-FET, suggesting its potential in clinical evaluations of brain tumors. Trial registration: ChiCTR2400081576, registration date: 2024–03-05, https://www.chictr.org.cn/bin/project/edit?pid=206162